Performance Analysis of CSR Implementation of PT. Golden Great Borneo Year 2021 in Lahat District - Susilo, Aris; Juniah, Restu; Taqwa, Ridhah (Journal Research of Social Science, Economics, and Management, 2022)
Corporate Social Responsibility (CSR) is an obligation that must be carried out by companies that manage natural resources. The Minister of Energy and Mineral Resources of the Republic of Indonesia number 1824 K/30/MEM/2018 requires every company to prepare a master plan for Community Development and Empowerment during the production and post-mining operations. PT. Golden Great Borneo is committed to implementing CSR according to these guidelines, with the aim of establishing good relations with the community around the mining area. This study aims to analyze the performance of the company's CSR implementation in 2021. Where that year was the first year the company carried out CSR with the guidance of the PPM master plan. This research was conducted using a transcript of interviews with the ring 1 community and the company. The analysis was conducted to see the performance of CSR implementation and its effect on the company's operations. The results of the analysis show that the company's CSR implementation performance will be good if it is supported by the competence of the company's CSR implementing team. Because this team will collect input suggestions, arrange activities, budget, activities, and carry out activities with beneficiaries. The CSR program run by the company referring to the Decree of the Minister of Energy and Mineral Resources of the Republic of Indonesia number 1824 K/30/MEM/2018 is running effectively with the percentage of budget realization reaching 121.45%. This good CSR performance has an indirect positive influence on the company's operational performance, especially at the level of the company's coal sales.